2016
DOI: 10.1523/jneurosci.3543-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Distinct β Band Oscillatory Networks Subserving Motor and Cognitive Control during Gait Adaptation

Abstract: Everyday locomotion and obstacle avoidance requires effective gait adaptation in response to sensory cues. Many studies have shown that efficient motor actions are associated with rhythm (8 -13 Hz) and ␤ band (13-35 Hz) local field desynchronizations in sensorimotor and parietal cortex, whereas a number of cognitive task studies have reported higher behavioral accuracy to be associated with increases in ␤ band power in prefrontal and sensory cortex. How these two distinct patterns of ␤ band oscillations interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
193
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(211 citation statements)
references
References 106 publications
15
193
3
Order By: Relevance
“…We anticipate that other researchers can deploy this same signature for stopping in scalp EEG to test the recruitment and timing of inhibitory control in other task contexts (c.f. van Gaal, et al, 2008; Wagner, et al, 2016). Accordingly, we provide companion material which shares the data and analysis stream.…”
Section: Resultsmentioning
confidence: 99%
“…We anticipate that other researchers can deploy this same signature for stopping in scalp EEG to test the recruitment and timing of inhibitory control in other task contexts (c.f. van Gaal, et al, 2008; Wagner, et al, 2016). Accordingly, we provide companion material which shares the data and analysis stream.…”
Section: Resultsmentioning
confidence: 99%
“…By using gait dynamics such as heel strikes to time-lock continuous EEG recordings, Gwin et al (2011) have reported increased power spectral activity in the left and right sensorimotor cortex during contralateral foot suspension in subjects walking at a steady pace on a treadmill, suggesting increased cortical involvement related to visuo-motor integration and error monitoring. More recently, Wagner et al (2016) reported different patterns of power spectral activity reflecting movement initiation and execution (Mu and Beta desynchronization in sensorimotor and parietal cortex) and motor control and inhibition (increased frontal Beta power) during a gait adaptation task. These important early findings demonstrate the feasibility of characterizing modulations of EEG activity in relation to body dynamics through the integration of brain and body measurements.…”
Section: The Emergence Of Mobile Methodsmentioning
confidence: 99%
“…Equally impressively, recent study successfully demonstrated the feasibility of parsing non-brain from brain signals in subjects cycling in a natural environment (Zink et al, 2016). Moreover, advanced EEG data analyses can be applied toward signal source localization based on the reconstruction of equivalent dipoles of independent components (Gramann et al, 2010; Wagner et al, 2016). However, EEG source modeling methods are essentially based on computational derivations and therefore require a feed of high-dimensional EEG data (i.e., 120+ channels) in order to reach sufficient approximations of signals' origins.…”
Section: Current Challengesmentioning
confidence: 99%
“…ICs were identified as outliers if their locations in the clustering vector space were larger than five times of standard deviation from the obtained cluster centers. Only clusters including ICs from more than half of the subjects (i.e., at least six subjects) were used for further analysis (Wagner et al, 2016). …”
Section: Methodsmentioning
confidence: 99%